Changing biological behaviour of NETs during the evolution of the disease: progress on progression. Issue 5 (29th April 2021) - Alexandraki, Krystallenia I; Spyroglou, Ariadni; Kykalos, Stylianos; Daskalakis, Kosmas; Kyriakopoulos, Georgios; Sotiropoulos, Georgios C; Kaltsas, Gregory A; Grossman, Ashley B
Abstract : Following improvements in the management and outcome of neuroendocrine neoplasms (NENs) in recent years, we see a subset, particularly of pancreatic NENs, which become more aggressive during the course of the disease. This is reflected by an increase in the Ki-67 labelling index, as a marker of proliferation, which may lead to an occasion of increase in grading, but generally does not appear to be correlated with histologically confirmed dedifferentiation. A systematic review of the literature was performed in PubMed, Cochrane Library, and Embase until May 2020 to identify cases that have behaved in such a manner. We screened 244 articles: only seven studies included cases in their cohort, or in a subset of the cohort studied, with a proven increase in the Ki-67 during follow-up through additional biopsy. In addition to these studies, we have also tried to identify possible pathophysiological mechanisms implicated in advanced NENs, although currently no studies appear to have addressed the mechanisms implicated in the switch to a more aggressive biological phenotype over the course of the disease. Such progression of the disease course may demand a change in the management. Summarising the overall evidence, we suggest that future studies should concentrate on changes in the molecular pathways during disease progression with sequential biopsies in order to shed light on the mechanisms that render a neoplasm more aggressive than its initial phenotype or genotype.